2016
DOI: 10.3390/nu8010036
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Dietary Intake Questionnaire Validation Conducted among Young Polish Women

Abstract: Due to inadequate intake of Vitamin D, identification of individuals characterised by the highest risk of deficiencies is one of the more crucial tasks for public health. The aim of the presented study was to assess the validity and reproducibility of the designed Vitamin D dietary intake questionnaire based on food frequency assessment—VIDEO-FFQ (VItamin D Estimation Only—Food Frequency Questionnaire) in a group of Polish women aged 20–30 years. Seventy-five participants kept a three-day dietary record and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 36 publications
2
58
0
Order By: Relevance
“…For the preconceived conditions, the minimum sample size was calculated as 35 individuals. The sampling procedure for validation was conducted as for the previous paper, while the number of participants was at an equal level [23]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the preconceived conditions, the minimum sample size was calculated as 35 individuals. The sampling procedure for validation was conducted as for the previous paper, while the number of participants was at an equal level [23]. …”
Section: Methodsmentioning
confidence: 99%
“…Validation of the obtained IRONIC-FFQ questionnaire was conducted according to methodology published previously [23]. It included an analysis of the validity (external validation comparing results of the FFQ1 with results of the 3-day dietary record, whereas both assessments were conducted by the same researcher) and reproducibility of the method (internal validation comparing results obtained twice—FFQ1 and FFQ2, with both assessments conducted by the same researcher), as defined by Willett and Lenart [26].…”
Section: Methodsmentioning
confidence: 99%
“…Higher intakes of LYC have been associated with a reduced fecal blood, mucus, and pus in subjects with ulcerative colitis in remission. [15] Likewise, animal studies of colitis have demonstrated a reduction in myeloperoxidase, a marker of colon inflammation, after LYC administration both with [16] or without [17] iron. One plausible mechanism of action is that LYC acts directly to protect the gastrointestinal lumen.…”
Section: Introductionmentioning
confidence: 99%
“…The study included the development of the semiquantitative brief FFQ to assess the magnesium intake (Mg-FFQ) and validation of the obtained FFQ in the Polish population of young women that was conducted using the same methodology as for previously developed brief FFQs for minerals [18][19][20] and vitamins. 21,22 The study was conducted according to the guidelines laid down in the Declaration of Helsinki, and all participants provided their informed consent to participate. All the procedures were approved by the Bioethical Commission of the National Food and Nutrition Institute in Warsaw (No.…”
Section: Methodsmentioning
confidence: 99%